Seed germination and antioxidant enzyme activity in seedlings of diploid and tetraploid bahiagrass under water restriction - Gabriel Streck Bortolin; Alfredo José Salinas-Arcienega; Yutcelia Carolina Galviz-Fajardo; Luciano do Amarante; Carlos Eduardo da Silva Pedroso; João Carlos Pinto Oliveira; Mauricio Marini Köpp; Andrea Bicca Noguez Martins; Lilian Vanussa Madruga de Tunes (Ciência Rural, 2020)
ABSTRACT: The objective of the following research was to investigate the physiological responses of two bahiagrass genotypes (Paspalum notatum Flügge) submitted to water restriction, induced by polyethylene glycol (PEG6000), during seed germination. Seeds of cv. Pensacola (diploid) and Bagual ecotype (tetraploid) were placed on paper moistened with osmotic solutions at potentials of 0.0; -0.1; -0.2 and -0.3 MPa. Composed of two subsamples of 100 seeds and four experimental units per treatment, the germination test was conducted in a germination chamber under alternating temperatures of 30 °C (8 hours) and 20 °C (16 hours), with presence of light during the higher temperature. Final germination percentage and germination speed index of the seeds, as well as early growth, activity and expression of antioxidant enzymes of seedlings were evaluated. The water restriction induced by PEG6000 reduced the percentage of germination in Pensacola (from 74% to 59%) and Bagual (34% to 10%). For the latter, the evaluation of seedlings showed higher dry mass in relation to cv. Pensacola (1.7 times higher in root and 1.6 times in shoot). In response to moderate water restriction, the genotypes showed increases in root growth (1.7 times higher in -0.1 compared to 0.0 MPa), both in expression and enzymatic activity (superoxide dismutase and catalase).